2007
DOI: 10.1042/ba20070038
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour activity of cationic‐liposome‐conjugated adenovirus containing the CCL19 [chemokine (C‐C motif) ligand 19] gene

Abstract: CCL19 [chemokine (C-C motif) ligand 19; also known as MIP-3beta (macrophage inflammatory protein-3beta) or ELC (Epstein-Barr-virus-induced molecule 1 ligand chemokine)], one of the immunostimulatory cytokines, chemoattracts both DCs (dendritic cells) and T-lymphocytes. Adenoviral vector is one of the most used gene delivery vectors for cancer therapy because of its high gene-transfection efficiency. However, its wider application is limited, owing to immune responses that reduce transgene expression and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Many reports have revealed that the expression of the chemokine receptor CCR7 on cancer cells induces metastasis to regional lymph nodes (Müller et al , 2001; Andre et al , 2006; Cabioglu et al , 2007; Koizumi et al , 2007). On the other hand, Cao et al (2007) reported an antitumour effect of CCL19. Therefore, we became interested in the function of the CCR7–ligands axis, which appears to be associated with both good and bad outcomes in cancer prognosis.…”
mentioning
confidence: 99%
“…Many reports have revealed that the expression of the chemokine receptor CCR7 on cancer cells induces metastasis to regional lymph nodes (Müller et al , 2001; Andre et al , 2006; Cabioglu et al , 2007; Koizumi et al , 2007). On the other hand, Cao et al (2007) reported an antitumour effect of CCL19. Therefore, we became interested in the function of the CCR7–ligands axis, which appears to be associated with both good and bad outcomes in cancer prognosis.…”
mentioning
confidence: 99%
“…The proteomic study by Yang et al [22] identified three serum candidate protein biomarkers for NSCLC: apolipoprotein C-I (ApoC-I), haptoglobin alpha-1 chain, and www.journals.viamedica.pl S100A4, which can diagnose NSCLC in patients with a sensitivity and specificity of 96.56% and 94.79%, respectively. ApoC-I is a lipid carrier protein and, although previous studies mainly focused on lipoprotein metabolism, it has been reported that the ApoC-I also regulates many cellular functions such as the promotion of growth factor-mediated cell survival and apoptosis [23]. It has been demonstrated that ApoC-I has a certain anticancer effect on tumor cells, as well as the ability to decrease the expression of PCNA, Ki-67 and Bcl-2 proteins, enhance Bax protein expression, and inhibit cell proliferation [24].…”
Section: Protein Diagnostic Biomarkers Detected In Nsclc Patientsmentioning
confidence: 99%
“…Liposomes, both cationic and anionic, have also been applied for encapsulation of Ad [146148]. Recently, Ad encapsulated in anionic liposomes demonstrated high transduction efficiency in a CAR-deficient cell line, evaded vector-specific NAbs and elicited lesser cytotoxicity as compared to Ad complexed with cationic liposomes [149].…”
Section: Strategies For Circumvention Of Vector Immunitymentioning
confidence: 99%